SACREDNESS AND VIOLENCE IN THE JURIDICO-DISCIPLINARY „DISPOSITIFS” - Ștefan VLAD (Studia Universitatis Babeș-Bolyai. Philosophia)
Sacredness and Violence in the Juridico-disciplinary Dispositifs. Sacredness and violence in the juridico-disciplinary dispositifs advances an analysis of sacredness as a strictly and eminently juridical and political phenomenon. Being the result of enforcing a value threshold beyond which human existence no longer posesses any juridical, economical or epistemic value, sacredness, as a matrix of the violent relation between power and the human body, reveals itself to be both the unveiling act of soveregin power and the crossing point between the juridical and the biopolitical power patterns. Following also Foucault’s distiction between subjectivation and assujetissment, we shall develop the analysis of a form af subjectification which, as a perpetual struggle against power, exceeds the power-knowledge nexus of juridical and biopolitical aparatuses.